Seasonal changes in the diet of Mute Swans Cygnus olor in the recently colonised eastern Gulf of Finland - Kouzov, Sergei A.; Gubelit, Yulia I.; Kravchuk, Anna V.; Koptseva, Elena M.; Zaynagutdinova, Elmira M.; Nikitina, Valentina N. (Wildfowl, 2021)
Mute Swans Cygnus olor have expanded their Russian breeding range since the 1950s, and first colonised the eastern part of the Gulf of Finland in 1987. Diet analysis showed that the pre-breeding and breeding season diet of Mute Swans in this region consists entirely of soft aquatic plants. In late winter and early spring (prior to active vegetation growth) the birds fed on the previous year’s growth of green filamentous algae Chladophora sp., which had been displaced by currents and storms from wintering mats on the bottom substrate. Diatoms were an increasingly important component of the swans’ diet during the pre-nesting period, from a month before egg-laying and also during egg-laying, when diatom abundance was peaking but the growth of vascular aquatic plants and algae had yet to commence. Later, during egg-laying and incubation, Mute Swans began to feed on the new season’s growth of aquatic vascular plants and filamentous algae. Given the timing of diatom intake, we suggest that diatoms can play a significant role in enabling Mute Swans in the eastern part of the Gulf of Finland to accumulate the protein and energy reserves required for reproduction.